Fostering Reading Interest in Elementary Students through Local Wisdom: A Case Study - Kustyamegasari, Arista; Hendratno; Heru Subrata; Wahyu Sukartiningsih; Nurul Istiq'faroh (Jurnal Elementaria Edukasia, 2025)
This pre-study explores the reading interest of elementary school students and the potential integration of local wisdom into literacy practices. The background of this study stems from preliminary findings that reveal low reading interest among second-grade students in an elementary school. Most students prefer picture books and show limited engagement with traditional texts, especially when lacking visual appeal. Furthermore, observations and teacher interviews indicate that cultural elements such as local traditions and values—particularly from Madura—are rarely included in classroom reading materials. Using a qualitative case study approach, data were collected through questionnaires, classroom observations, and teacher interviews. The results show that 70% of students read only when instructed, and over 80% express interest in books that include illustrations and culturally familiar content. Teachers acknowledge the need for relevant reading materials that combine engaging storytelling with the richness of local culture. They believe such materials can promote reading habits while strengthening students’ cultural identity. This study highlights a significant gap in culturally responsive reading materials for young learners. It suggests the importance of developing culturally integrated picture storybooks to enhance reading interest. Incorporating local wisdom into early literacy development can not only foster students’ engagement in reading but also preserve cultural heritage. The findings provide a basis for future development of reading materials rooted in local traditions and values.